Pyroptosis-driven immune dysregulation in COPD: molecular mechanisms and therapeutic implications - Ni, Feng-Xian; Wang, Hui-Xian; Hu, Jie; Chen, Pei-Sheng; Huang, Hua-Jing; Chen, Hui-Hui; Huang, Dong-Hui; Jiang, Ze-Bo (Frontiers in Immunology, 2025)
Pyroptosis, a programmed cell death mechanism mediated by gasdermin proteins such as GSDMD, is typically activated by inflammasomes. While essential for host defense against infections, excessive pyroptosis contributes to chronic inflammation and exacerbates inflammatory diseases. In chronic obstructive pulmonary disease (COPD), dysregulated pyroptosis interacts with immune cells—including neutrophils, macrophages, and T lymphocytes—to perpetuate inflammation, tissue damage, and acute exacerbations. This review explores the molecular mechanisms of pyroptosis, its cell-type-specific roles in COPD pathogenesis, and its implications for therapeutic targeting. By synthesizing evidence from primary research, we highlight how pyroptosis influences immune dysregulation in COPD and propose novel strategies for disease management.